Social Spending in Korea : Can it Foster Sustainable and Inclusive Growth? - Elekdag, Selim (Washington, D.C. : International Monetary Fund, 2012)
Going forward, Korea faces two closely related challenges: sustaining economic growth against the backdrop of a rapidly aging population and ameliorating income inequality. This paper argues that a gradual increase in social spending could promote more sustainable and inclusive growth in Korea. In particular, simulation results suggest that social spending which supports labor market reforms can boost longer-term growth. However, despite rapid increases recently-albeit from a low base-there is still a social spending gap relative to Korea's OECD peers. Because of several fiscal challenges in the coming decades, increases in social spending should be incremental, and would be usefully guided by a longer-term fiscal framework.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet